Psychotic disorder and educational achievement: a family-based analysis - Frissen, Aleida; Lieverse, Ritsaert; Marcelis, Machteld; Drukker, Marjan; Delespaul, Philippe; GROUP Investigators; Cahn, W (D. Steinkopff-Verlag, 2015)
BACKGROUND: Early social and cognitive alterations in psychotic disorder, associated with familial liability and environmental exposures, may contribute to lower than expected educational achievement. The aims of the present study were to investigate (1) how differences in educational level between parents and their children vary across patients, their healthy siblings, and healthy controls (effect familial liability), and across two environmental risk factors for psychotic disorder: childhood trauma and childhood urban exposure (effect environment) and (2) to what degree the association between familial liability and educational differential was moderated by the environmental exposures. METHODS: Patients with a diagnosis of non-affective psychotic disorder (n = 629), 552 non-psychotic siblings and 326 healthy controls from the Netherlands and Belgium were studied. Participants reported their highest level of education and that of their parents. Childhood trauma was assessed with the Dutch version of the Childhood Trauma Questionnaire-Short Form. Urban exposure, expressed as population density, was rated across five levels. RESULTS: Overall, participants had a higher level of education than their parents. This difference was significantly reduced in the patient group, and the healthy siblings displayed intergenerational differences that were in between those of controls and patients. Higher levels of childhood urban exposure were also associated with a smaller intergenerational educational differential. There was no evidence for differential sensitivity to childhood trauma and childhood urbanicity across the three groups. CONCLUSION: Intergenerational difference in educational achievements is decreased in patients with psychotic disorder and to a lesser extent in siblings of patients with psychotic disorder, and across higher levels of childhood urban exposure. More research is required to better understand the dynamics between early social and cognitive alterations in those at risk in relation to progress through the educational system and to understand the interaction between urban environment and educational outcomes.
Keywords: Psychosis; Cognition; Education; Trauma; Urbanicity